Spatial characteristics analysis of community conflicts in Zhangjiajie National Forest Park - Yurong, Wu; Bidin, Sheena; Johari, Shazali (Routledge, 2025)
Community conflicts in tourism destinations often stems from a complex interplay of multi scale factors that includes geographical conditions, socioeconomic dynamics, and management of resources. This study adopted a hybrid approach to investigate the spatial distribution of community conflicts in Zhangjiajie National Forest Park. A questionnaire survey was conducted among 358 residents, and conflict points were marked using a participatory Geographic Information System (PGIS), including semi-structured interviews with 32 residents. The analysis reveals six primary conflict categories, with inequitable benefit distribution and conservation-development disputes emerging as the most predominant issues. Significant spatial dynamics are observed, particularly in resident-manager (47.81%) and resident-operator (25.71%) conflicts. This research contributes to conflict theory by elucidating the spatial dimensions of community disputes in ecotourism contexts, highlighting the interplay between local stakeholder dynamics and resource management. The findings advocate for integrated conflict management strategies that engage local communities, promoting equitable tourism practices and sustainable governance in national parks.